Effects of fluoride on proliferation and mineralization in periodontal ligament cells in vitro - Li,K.Q. (2016)
Fluoride, which is often added to toothpaste or mouthwash in order to protect teeth from decay, may be a novel therapeutic approach for acceleration of periodontal regeneration. Therefore, we investigated the effects of fluoride on proliferation and mineralization in human periodontal ligament cells in vitro. The periodontal ligament cells were stimulated with various concentrations of NaF added into osteogenic inductive medium. Immunohistochemistry of cell identification, cell proliferation, alkaline phosphatase (ALP) activity assay, Alizarin red S staining and quantitative real-time-polymerase chain reaction (RT-PCR) were performed. Moderate concentrations of NaF (50-500 μmol/L) had pro-proliferation effects, while 500 μmol/L had the best effects. ALP activity and calcium content were significantly enhanced by 10 μmol/L NaF with osteogenic inductive medium. Quantitative RT-PCR data varied in genes as a result of different NaF concentrations and treatment periods. We conclude that moderate concentrations of NaF can stimulate proliferation and mineralization in periodontal ligament cells. These in vitro findings may provide a novel therapeutic approach for acceleration of periodontal regeneration by addition of suitable concentrations of NaF into the medication for periodontitis treatment, i.e., into periodontal packs and tissue patches.